2010
DOI: 10.1590/s0006-87052010000300003
|View full text |Cite
|
Sign up to set email alerts
|

Seleção de híbridos diplóides (AA) de bananeira com base em três índices não paramétricos

Abstract: RESUMOObjetivou-se selecionar híbridos diplóides (AA) de bananeira com base em três índices não paramétricos, a fim de orientar a seleção e aumentar o aproveitamento da variabilidade existente no Banco de Germoplasma de Bananeira da Embrapa Mandioca e Fruticultura Tropical. Foram avaliados 11 híbridos, no delineamento de blocos ao acaso, com quatro repetições. As parcelas constituíram-se de seis plantas, espaçadas de 2,5 m x 2,5 m, tendo na bordadura plantas da cultivar Pacovan. Tomaram-se dados dos seguintes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 10 publications
2
13
0
2
Order By: Relevance
“…Similar results, regarding the two methodologies, were also found by Lessa et al, (2010), aiming to select diploid hybrids (AA) of banana using three non-parametric indices; they concluded that the indices of Elston (1963), Mulamba & Mock (1978) and Schwarzbach (1972, as cited in Wricke & Weber, 1986 were efficient to rank the diploid banana hybrids, however, the first two indices provided a better ranking.…”
Section: Resultssupporting
confidence: 63%
“…Similar results, regarding the two methodologies, were also found by Lessa et al, (2010), aiming to select diploid hybrids (AA) of banana using three non-parametric indices; they concluded that the indices of Elston (1963), Mulamba & Mock (1978) and Schwarzbach (1972, as cited in Wricke & Weber, 1986 were efficient to rank the diploid banana hybrids, however, the first two indices provided a better ranking.…”
Section: Resultssupporting
confidence: 63%
“…Another studies also report superiority of this index for alfalfa (VASCONCELOS et al, 2010), soybean (BÁRBARO et al, 2007), yellow passion fruit (ROSADO et al, 2012), popcorn (AMARAL JÚNIOR et al, 2010), cowpea (BERTINI et al, 2010), maize (RODRIGUES et al, 2011) and banana (LESSA et al, 2010).…”
Section: Resultsmentioning
confidence: 90%
“…The indexes that require estimates of genetic parameters are known as parametric indexes and are used in specifi c situations, being suitable when the genotypes form a random sample of the population (LESSA et al, 2010). For cases that involve genotypes that have already passed through the selective process (fi xed samples), the nonparametric index group exists, which does not require estimates of genetic parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most SI categories are obtained by maximizing the correlation between the genotypic value and the index, aiming at the maximum selection efficiency. The most commonly used SI are those based on ANOVA, the predicted genotypic values, the parametric and nonparametric indices (Vieira et al, 2006;Pedrozo et al, 2009;Lessa et al, 2010;Pinto et al, 2013). The latter have been adopted by selection processes in various crops (Garcia and Souza Jr., 1999;Amaral Júnior et al, 2010;Rosado et al, 2012).…”
Section: Introductionmentioning
confidence: 99%